Wittgenstein reads Weininger - Stern, David G.; Szabados, Béla 1942- (Cambridge University Press, 2004)
Otto Weininger was one of the most controversial and widely read authors of fin-de-siècle Vienna. He was both condemned for his misogyny, self-hatred, anti-semitism and homophobia, as well as praised for his uncompromising and outspoken approach to gender and morality. For Wittgenstein Weininger was a 'remarkable genius'. He repeatedly recommended Weininger's Sex and Character to friends and students and included the author on a short list of figures who had influenced him. The purpose of this new collection of essays is to explore the various ways in which Wittgenstein absorbed and responded to Weininger's ideas. Written by an international team of experts on Wittgenstein and Weininger, the volume is especially timely in the light of recent translations of Weininger's work and will appeal to anyone interested in the history of 20th century philosophy, and the literary and cultural history of fin-de-siècle Vienna
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Weininger, Otto / 1880-1903 / Influence; Wittgenstein, Ludwig / 1889-1951; Wittgenstein, Ludwig -- 1889-1951; Weininger, Otto -- 1880-1903; Rezeption